Analisis Data Citra Buah Buahan Dengan Algoritma Fagin Dan Threshold - A. Haris Rangkuti; Marimin Marimin; Kudang Boro Seminar (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2008)
There are different ways of obtaining and accessing information in a multimedia database thaninformation in a traditional database. For example, in a multimedia database, it might be reasonable to have aquery that asks for, say, the top 10 images that are similar to a fixed image. Beside a multimedia database mightdeal with pictures that have a complicated coloring pattern and that contain a number of shapes. Thesedifferences lead to fundamental differences between multimedia queries and standard relational databasequeries. Unlike the situation in relational databases, where the semantics of a Boolean combination is quiteclear, in multimedia databases it is not at all clear what the semantics is of even the conjunction of atomicqueries. Because of that our experiments on this research show that there are some algorithm support to accessmultimedia database, but two of them what we concern are fagin algorithm and threshold algorithm. For thisresearch there are 2 sides of fruit Citra what we have to concern. There are shape and color of fruit image. Forcolor of fruit we are using histogram function, and for shape of fruit we are using binary image function.Keywords: Multimedia Database, Traditional Database, Fagin algorithm, Threshold algorithm, ColoringPattern, Histogram Function, Binary Image.